الخط العربي تاريخ و إبداع (Arabic Calligraphy, History and Creativity) - كريمة مبدوعة (Universitas Negeri Malang, 2023)
The educational reality that falls during the primary period is the basic rule that build the educational status for the pupil. In fact, it is during the period that pupils learn the basics of the Arabic calligraphy, which is the main branch of the Arabic language. Moreover, this skill helps à lot the pupil in character building and Development. In fact, this is the title of our study. In this research: At which extend can we activate the education of the Arabic Calligraphy through the first grade stages? Some secondary questions can derive from this title: - How do we teach the Arabic calligraphy during the primary period? What are the obstacles that teachers meet to transmit calligraphy to the learner? What are the obstacles the learners face during learning the Arabic calligraphy? What me the suggested solutions for this problems and obstacles. We have based our analysis on the descriptive and analytical method for it is suitable for this kind of subject to describe an interpret this phenomenon